ANAK PUTUS SEKOLAH (STUDI DI MASYARAKAT DESA SETELUK KABUPATEN SUMBAWA BARAT) - Elmi Arsita; Syafruddin Syafruddin; Muhammad Ilyas (Jurnal Pendidikan Sosial Keberagaman, 2022)
This study aims to determine: (1) the factors that cause children to drop out of school; (2) the impact of children dropping out of school and (3) efforts to overcome dropouts in Seteluk Village, Seteluk Sub-district, KSB. This research uses a qualitative approach with a case study method. Data collection techniques in this study using interviews, observation and documentation. The results of this study found (1) the factors that cause children to drop out of school are low interest or willingness of children to go to school, schools are considered unattractive, inability to attend lessons, family economic conditions, lack of parental attention, less supportive environment, and less harmonious parental relationships. ; (2) There are four negative impacts of dropping out of school in Seteluk Village, namely limited insight or knowledge in children, having a sense of inferiority, children's emotional maturity will be increasingly hampered and become unemployed; (3) Efforts to overcome dropouts in Seteluk Village can be carried out, namely parents monitoring academic abilities, parents paying attention to children's personalities, providing scholarships and free school assistance for underprivileged children, increasing the role of the government in solving educational problems, and infrastructure development programs that evenly so that the Seteluk Village community can hone their skills and knowledge.